Cost-effectiveness of a combined classroom curriculum and parental intervention: economic evaluation of data from the Steps Towards Alcohol Misuse Prevention Programme cluster randomised controlled trial. Issue 7 (2nd July 2019) - Agus, Ashley; McKay, Michael; Cole, Jonathan; Doherty, Paul; Foxcroft, David; Harvey, Séamus; Murphy, Lynn; Percy, Andrew; Sumnall, Harry
Abstract : Objectives: This study aimed to assess the cost-effectiveness of the Steps Towards Alcohol Misuse Prevention Programme (STAMPP) compared with education as normal (EAN) in reducing self-reported heavy episodic drinking (HED) in adolescents. Design: This is a cost-effectiveness analysis from a public sector perspective conducted as part of a cluster randomised trial. Setting: This study was conducted in 105 high schools in Northern Ireland and in Scotland. Participants: Students in school year 8/S1 (aged 11–12) at baseline were included in the study. Interventions: This is a classroom-based alcohol education curricula, combined with a brief alcohol intervention for parents/carers. Outcome measures: The outcome of this study is the cost per young person experiencing HED avoided due to STAMPP at 33 months from baseline. Results: The total cost of STAMPP was £85 900, equivalent to £818 per school and £15 per pupil. Due to very low uptake of the parental component, we calculated costs of £692 per school and £13 per pupil without this element. Costs per pupil were reduced further to £426 per school and £8 per pupil when it was assumed there were no additional costs of classroom delivery if STAMPP was delivered as part of activities such as personal, social, health and economic education. STAMPP was associated with a significantly greater proportion of pupils experiencing a heavy drinking episode avoided (0.08/8%) and slightly lower public sector costs (mean difference −£17.19). At a notional willingness-to-pay threshold of £15 (reflecting the cost of STAMPP), the probability of STAMPP being cost-effective was 56%. This level of uncertainty reflected the substantial variability in the cost differences between groups. Conclusions: STAMPP was relatively low cost and reduced HED. STAMPP was not associated with any clear public sector cost savings, but neither did it increase them or lead to any cost-shifting within the public sector categories. Further research is required to establish if the cost-effectiveness of STAMPP is sustained in the long term. Trial registration number: ISRCTN47028486 ; Results.